The challenges of epidemiologic translation: communicating with physicians, policymakers, and the public - Levin, Jeff (Frontiers in Public Health, 2024)
Translational epidemiology refers to the practical application of population-health research findings to efforts addressing health disparities and other public health issues. A principal focus of epidemiologic translation is on the communication of results to constituencies who can best make use of this information to effect positive health-related change. Indeed, it is contended that findings from epidemiologic research are of greatest use only if adequately communicated to health professionals, legislators and policymakers, and the public. This paper details the challenges faced by efforts to communicate findings to the these constituencies, especially three types of miscommunication that can derail efforts at translation. These include perceived misinformation, perceived disinformation, and perceived censorship. Epidemiologists are ethically obliged to avoid these types of miscommunication, and, accordingly, are advised to place greater emphasis on messaging and media outreach to physicians, government officials, medical educators, and the general public.